The Role of Education in Purging Violence and Immoral Acts in Individual and Social Upbringing - Goudarzi, Zahra; Sarmadi, Mohammad Reza; Rezaei, Mohammad Hashem (Journal of History Culture and Art Research, 2017)
Abstract This research examines the role of education in purging violence and preventing immoral acts in individual and social upbringing. According to the content of this research, we can acknowledge this: education is the process of notifying the trainee and caring for him in a manner that he is accustomed to some behaviors and abandons some of them, and also recognizes behavioral trauma and errors. The child develops a behavioral pattern. Therefore, he does what he observes in a family environment, including mother and father and the other members of the family. Gradually, he grows and enters a larger setting: school. The important point in here is the role of adopting pattern from one’s peers, teacher, and teaching staff, including the principal also seems essential. Furthermore, the child, who is called student in here, directly receives instructions and develops recognition regarding values and disvalues. He finds that if he shows a disvalued behavior, it is called an abnormal behavior. This type of behavior appears in various forms, including social personality disorders. Since abnormal and disvalued behavior is an anti-social phenomenon and bears many losses (life and property), the government attempts to oppose this anti-social phenomenon. In this research, the dimensions and types of violence are studied. This study suggests that the school, as a bridge between family and society, would have a more effective role in education and preventing violence.